Outcomes Analysis of Biologic Mesh Use for Abdominal Wall Reconstruction in Clean-Contaminated and Contaminated Ventral Hernia Repair. Issue 2 (August 2015) - Sbitany, Hani; Kwon, Edwin; Chern, Hueylan; Finlayson, Emily; Varma, Madhulika G.; Hansen, Scott L.
<x xml:space="preserve">Abstract</x> Background Repair of grade 3 and grade 4 ventral hernias is a distinct challenge, given the potential for infection, and the comorbid nature of the patient population. This study evaluates our institutional outcomes when performing single-stage repair of these hernias, with biologic mesh for abdominal wall reinforcement. Methods A prospectively maintained database was reviewed for all patients undergoing repair of grade 3 (potentially contaminated) or grade 4 (infected) hernias, as classified by the Ventral Hernia Working Group. All those patients undergoing repair with component separation techniques and biologic mesh reinforcement were included. Patient demographics, comorbidities, and postoperative complications were analyzed. Univariate analysis was performed to define factors predictive of hernia recurrence and wound complications. Results A total of 41 patients underwent single-stage repair of grade 3 and grade 4 hernias during a 4-year period. The overall postoperative wound infection rate was 15%, and hernia recurrence rate was 12%. Almost all recurrences were seen in grade 4 hernia repairs, and in those patients undergoing bridging repair of the hernia. One patient required removal of the biologic mesh. Those factors predicting hernia recurrence were smoking (P = 0.023), increasing body mass index (P = 0.012), increasing defect size (P = 0.010), and bridging repair (P = 0.042). No mesh was removed due to perioperative infection. Mean follow-up time for this patient population was 25 months. Conclusions Single-stage repair of grade 3 hernias performed with component separation and biologic mesh reinforcement is effective and offers a low recurrence rate. Furthermore, the use of biologic mesh allows for avoidance of mesh explantation in instances of wound breakdown or infection. Bridging repairs are associated with a high recurrence rate, as is single-stage repair of grade 4 hernias.